RSMeans Estimating Handbook. - Sillah, Andrea (R.S. Means Company, Incorporated John Wiley & Sons, Incorporated [distributor], 2009)
Annotation This handbook simplifies the task of evaluating construction plans and specs to arrive at a reliable quantity calculation for pricing. It reflects the variety of technical data involved in the estimating process, including sizing, equipment requirements, and hundreds of other factors.
Keywords: Building -- Estimates -- Handbooks, manuals, etc.; elektronické knihy; electronic books